Beyond Accommodation: Reconstructing an Inclusive Assessment Framework for Children with Special Needs in Indonesian Madrasahs - Ninik Uswatun Fadilah; I Gede Ratnaya; I Dewa Ayu Made Budhyani; I Gusti Lanang Agung Parwata (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Inclusive education requires assessment systems that not only ensure access to learning but also promote justice in recognizing learners’ diverse abilities and ways of learning. However, assessment practices in Indonesian madrasahs remain dominated by uniform standards and homogeneous indicators, potentially reproducing academic exclusion among children with special needs. This study examines how conventional assessment practices generate academic exclusion, analyzes the limitations of accommodation-based approaches, and reconstructs a more adaptive and equitable framework for inclusive assessment in madrasahs. Using a qualitative approach based on secondary data and a critical qualitative review design, data from scholarly publications, policy documents, educational regulations, and related sources were analyzed through reflexive thematic analysis and critical discourse analysis. The findings indicate that academic exclusion is driven less by learners’ characteristics than by assessment designs emphasizing uniformity and standardization. Although accommodation-based approaches reduce participation barriers, they remain insufficient for achieving substantive assessment justice because they preserve the dominant evaluative paradigm. The study proposes an adaptive inclusive assessment framework integrating distributive, procedural, and recognitional justice, evaluative flexibility, participatory governance, and system reflexivity, providing a conceptual foundation for more responsive assessment policies and practices in madrasahs.